Implementing information commons: the challenges and prospects for Nigerian academic libraries (2015)
Information Commons has in recent times made a sudden, dramatic and wide spread appearance in academic and research libraries in the developed countries. Despite its high potential to boost scholarship, improve research quality and enhance library patronage, information commons is not in Nigerian academic library presently. This paper focus the prospects and challenges of implementing information commons in Nigerian academic libraries. As the seeking patterns and expectations of users continued to be tremendously influenced by innovations in ICT, creation of Information Commons would improve service delivery to patrons. The paper identified inhibiting factors that would challenge the adoption and creation of information commons in libraries. These include inadequate funding, poor literacy skills of staff, poor broadband access, weak ICT policy plan and weak institutional support. Considering the prospects of implementing information commons, Nigerian academic libraries were admonished to start working towards creating information commons to increase library patronage.